Oral contraceptive pills and possible adverse effects - Stone, Rebecca H (2014)
Oral contraceptive pills (OCPs) containing estrogen and progestin or progestin only were introduced as a contraceptive option for women in 1960. Since their introduction to the market, there have been significant changes in the drug content and formulations of these products, in part to decrease the risk of adverse effects. The OCP products available today, particularly combined oral estrogen and progestin products (COCs), continue to be widely used. The major adverse effect associated with COCs is an increased risk of a cardiovascular event. COCs are contraindicated for women with increased cardiovascular risk, increased thromboembolic risk, significant liver disease, systemic lupus erythematosus, or migraine with aura. In addition, both COCs and progestin-only pills (POPs) are contraindicated in patients with a personal history of breast cancer. Commonly reported minor adverse effects may include menstrual bleeding pattern changes, breast tenderness, headache, mood changes, and nausea. Frequently these minor adverse effects subside following the initial 3 months of appropriately administered therapy, and otherwise may be managed by changing the hormone strength or product formulation and confirming patient adherence. It is imperative that providers are familiar with the potential adverse effects associated with OCP use, so they may in turn educate and counsel patients. Since adverse effects are the primary reason for OCP discontinuation, it is critical that patients are made aware of and expect these in advance and are counseled how to minimize or manage adverse effects. It is important to note that many women also use OCPs for noncontraceptive benefits, such as regulating menstrual irregularities, treatment of premenstrual syndrome, prevention of menstrual migraine, treatment of acne, and others.